PENGARUH MOTIVASI BELAJAR DAN LINGKUNGAN TEMAN SEBAYA TERHADAP MINAT MEMBACA MAHASISWA PAP FKIP UNS ANGKATAN 2017 – 2019 - Annisaa Kultsum; Wiedy Murtini; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
Abstract The purpose of this research is to find out: 1) the effect of learning motivation on students reading interests, 2) the effect of peer environment on students reading interests, and 3) the effect of learning motivation and peer environment on students reading interests. This study used quantitative descriptive research with correlational methods. The population in this study is students of Office Administration Education class of 2017-2019. The research sample was taken by proportionate stratified random sampling techniques which amount to 147 students. Data collection techniques using questionnaires and interviews. Data analysis techniques were using multiple linear regression analysis with IBM SPSS 25 programs. The results showed that: 1) there is a significant influence of learning motivation on reading interests. This is evidenced by the results of thitung (4.785) > ttabel (1,976) and significance values (0.000 < 0.05); 2) there is a significant influence of peer environment on reading interests. This is evidenced by thitung (2,009) > ttabel (1,976) and significance values (0.046 < 0.05); and 3) there is a significant influence on learning motivation and peer environment together on reading interests. This is evidenced by the results of Fhitung (15,896) > Ftabel (3.06) and significance values (0.000 < 0.05).